2000
DOI: 10.1053/rmed.2000.0816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally-occurring acid fog on inflammatory mediators in airway and pulmonary functions in asthmatic patients

Abstract: Floating fog occurs every summer in Kushiro City in Japan, and the annual average of fog water pH in the past 4 years has been under 5.0. We previously reported that epidemiologically fog was the most important positive factor contributing to increased hospital visits of asthmatic patients compared with other meteorological values and air pollutants. This study aimed to investigate the mechanism of the effects of naturally-occurring acid fog on asthmatic patients. We compared pulmonary functions and inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…lism increases F e NO acutely in vivo but depletes airway GSNO levels long-term, decreasing F e NO; indeed, GSNO metabolism is increased in many patients with asthma. 32,33,[36][37][38][39] Single nucleotide polymorphisms in GSNO metabolic enzyme, GSNO reductase, are predictive of asthma, 38,40 and mice defi cient in GSNO reductase are protected from experimental asthma. 41 Note in this regard that GSNO reductase activity can be induced by allergen exposure and can result in increased methacholine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lism increases F e NO acutely in vivo but depletes airway GSNO levels long-term, decreasing F e NO; indeed, GSNO metabolism is increased in many patients with asthma. 32,33,[36][37][38][39] Single nucleotide polymorphisms in GSNO metabolic enzyme, GSNO reductase, are predictive of asthma, 38,40 and mice defi cient in GSNO reductase are protected from experimental asthma. 41 Note in this regard that GSNO reductase activity can be induced by allergen exposure and can result in increased methacholine responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, decreased airway pH recapitulates many features of asthma. 1,2,7,[30][31][32][33] Airway pH appears to be normally distributed in the general population, measured at a retail outlet store, 34 though outliers with low pH might be explained if some of the subjects had unreported asthma, GER, or intercurrent infections. 11,12,16,19 Here, we report that EBC pH in a large cohort with wellcharacterized severe and nonsevere asthma is, on the whole, normal.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous recent studies have suggested alterations in airway pH contribute to the pathophysiology of obstructive airway disease (reviewed in Ricciardolo et al ., 2004). Airway acidification caused by either exogenous acids (polluted air constituting an ‘acid fog’) (Honma et al ., 2000), endogenous acids (gastroesophageal reflux with microaspiration) (Ricciardolo, 2001; Hunt and Gaston, 2008), or as a consequence of airway inflammation (Kostikas et al ., 2002; Brunetti et al ., 2008) can reduce the pH of the airway and increase airway smooth muscle (ASM) contractility and airway resistance. Two major mechanisms mediating acid‐induced bronchoconstriction have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Clouds and fog play an important role as processors of atmospheric aerosols and soluble gases. Concerns are increasing about adverse effects of fog on respiratory function and airway response in asthmatics (Honma et al, 2000;Fontana et al, 2002). Urban air particulate material (APM) is a complex mixture of chemicals released from vehicular and industrial sources, together with oil fumes from house cooking and re-entrained particles from roads.…”
Section: Introductionmentioning
confidence: 99%